2008
DOI: 10.1177/0894845308325644
|View full text |Cite
|
Sign up to set email alerts
|

Academic Transitions in Education

Abstract: Becoming and being a faculty is a dynamic journey defined by various career transitions, such as moving up through promotion and tenure, moving on to other institutions, and sometimes moving out of the academy altogether. This longitudinal qualitative study explored women faculty experiences of academic transitions and their impact on faculty identity development and transformation. Using the constant comparative method, the authors analyzed multiple interviews with 23 female faculty members in education, focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 26 publications
(31 reference statements)
0
21
0
1
Order By: Relevance
“…Reybold and Alamia 2008), there is none that does what our research does: follow individuals as they transition from postdoctoral to pre-tenure roles. A longitudinal approach is powerful in documenting identity as a dynamic journey of 'continuous self-definition of potential, achievement and expectation' (Reybold and Alamia 2008, 114).…”
Section: Conceptual Frameworkmentioning
confidence: 78%
“…Reybold and Alamia 2008), there is none that does what our research does: follow individuals as they transition from postdoctoral to pre-tenure roles. A longitudinal approach is powerful in documenting identity as a dynamic journey of 'continuous self-definition of potential, achievement and expectation' (Reybold and Alamia 2008, 114).…”
Section: Conceptual Frameworkmentioning
confidence: 78%
“…This transition for some female academics is crucial as a sign of professional growth and can be seen as an opportunity to transform their practice. As confirmed by Reybold and Alamia (2008), the journey in academia is fluid and not static. People are not automatically appointed academics when they accept their first positions.…”
Section: What Are Transitions?mentioning
confidence: 98%
“…Based on her research Hoskins (2010) additionally found that success was understood as involving women faculty achieving higher ranks in standard academic roles (from Lecturer to Senior Lecturer to Associate Professor, and Professor) and in relation to formal leadership positions. The latter could include management positions such as Rectors, Deans, Vice-Deans, and Heads of Department (Reybold & Alamia, 2008).…”
Section: Female Academics' Career Development Under New Managerialismmentioning
confidence: 99%
See 2 more Smart Citations